Heterojunction bilayers serving as a charge transporting interlayer reduce the dark current and enhance photomultiplication in organic shortwave infrared photodetectors. Issue 8 (1st June 2022) - Shin, Chanho; Li, Ning; Seo, Bogyeom; Eedugurala, Naresh; Azoulay, Jason D.; Ng, Tse Nga
Abstract : This work modifies the charge-transporting layer in organic photodiodes to a heterojunction bilayer. The bilayer design facilitates photomultiplication and suppresses the dark current to enhance detectivity and contrast in upconversion imagers. Abstract : Previous approaches to induce photomultiplication in organic diodes have increased the photosignal but lacked control over reducing background noise. This work presents a new interlayer design based on a heterojunction bilayer that concurrently enables photomultiplication and suppresses the dark current in organic shortwave infrared detectors to improve the overall detectivity. The heterojunction bilayer consists of a hole-transporting material copper thiocyanate and an electron-transporting material tin oxide, and this combination offers the ability to block charge injection in the dark. Under illumination, the bilayer promotes trap-assisted photomultiplication by lowering the tunneling barrier and amplifying the photocurrent through the injection of multiple carriers per absorbed photon. Upon incorporating the heterojunction interlayer in photodiodes and upconversion imagers, the devices achieve an external quantum efficiency up to 560% and a detectivity of 3.5 × 10 9 Jones. The upconversion efficiency of the imager doubles with a 1.7 fold improvement in contrast compared to the imager without the heterojunction interlayer. The new interlayer design is generalizable to work with different organic semiconductors, making it attractive and easy to integrate with emerging organic infrared systems.